Hubungan Motivasi Belajar dan Kecemasan Berbahasa terhadap Keterampilan Mengalihbahasakan Bahasa Korea-Indonesia - Muhaimin, Ki Agus Ahmad; Samsudin, Didin; Azizah, Asma (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the correlation between learning motivation and language anxiety with the ability to interpretation Korean-Indonesian. Correlation and ex-post facto research were used in this quantitative study. This research is completed by 36 undergraduate 4th year students of the Korean Education Study Program in Indonesia University of Education who had completed Korean for Science Technology course. The Likert-scale questionnaire on learning motivation using indicators of learning motivation (Uno, 2018), language anxiety using aspects of language anxiety (Horwitz, 1986), were used to collect the data for this research. Document analysis was used to analyze their final score in Korean for Science Technology course. The research results showed that there is a positive and significant correlation between learning motivation and Korean-Indonesian language interpretation ability, there is a significant negative relationship between language anxiety and Korean-Indonesian interpretation ability, there is a positive and not significant correlation simultaneously learning motivation and language anxiety with Korean-Indonesian interpretation ability. Learning motivation and language anxiety are the inner variable that functions as a stimulus and gives an effect on the students ability.